Responsible Drone Journalism - Gynnild, Astrid; Uskali, Turo (Disruptions, 2018)
"Camera drones provide unique visual perspectives and add new dimensions to storytelling and accountability in journalism. Simultaneously, the rapidly expanding uses of drones as advanced sensor platforms raise new legislative, ethical and transparency issues. Responsible Drone Journalism investigates the opportunities and dilemmas of using drones for journalistic purposes in a global perspective. Drawing on a framework of responsible research and innovation (RRI), the book explores responsible drone journalism from multiple perspectives, including new cultures of learning, flying in lower airspace, drone education and concerns about autonomous agents and big data surveillance. By widening the discussion of drone journalism, the book is ideal for journalism teachers and students, as well as politicians, lawmakers, drone developers and citizens with an interest in the responsible use of camera drones."